Peran Pajak Hotel: Kontribusi dan Efektivitas di Kota Samarinda dalam Menarik Wisatawan - Rinaldi, Muhammad; Ramadhani, Muhammad Harits Zidni Khatib; Ramadhani, Melda Aulia (Penerbit Goodwood, 2025)
Purpose: This study aims to analyze both the contribution and collection effectiveness of hotel tax revenue for PAD in Samarinda City. The research focuses on determining the extent to which hotel tax contributes to the city’s PAD and evaluating the effectiveness of the hotel tax collection process by comparing the actual revenue (realization) to the officially set revenue targets during the study period. Methodology/Approach: This study employs a quantitative descriptive approach using secondary data from 2015 to 2022, and analysis was conducted using ratio techniques to measure hotel tax contribution to PAD and the effectiveness of tax collection. Results/Findings: The findings reveal that Although hotel tax revenue in Samarinda has shown annual growth, its contribution to PAD remains relatively low, ranging from 4.97% to 6.63%. In contrast, the effectiveness ratio of hotel tax collection consistently exceeds 100%, indicating that revenue targets are being met or surpassed. Conclusion: Although the hotel tax collection process in Samarinda is effective, its contribution to PAD remains limited. One of the key challenges affecting hotel tax revenue is the underdeveloped tourism sector, which affects the hotel occupancy rate and ultimately limits tax revenue growth.. Limitations: This study is limited to data from 2015 to 2019 and does not account for recent policy changes in regional taxation. Contribution: This study contributes to the field of regional finance and taxation by providing empirical insights into the effectiveness and role of hotel tax revenue in supporting local financial independence